2016
DOI: 10.1002/ajh.24403
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection does not impact on survival or time to first treatment in patients with chronic lymphocytic leukemia

Abstract: Human cytomegalovirus (HCMV) is a widely prevalent herpes virus which establishes a state of chronic infection. The establishment of CMV‐specific immunity controls viral reactivation and leads to the accumulation of very large numbers of virus‐specific T cells which come to dominate the immune repertoire. There is concern that this may reduce the immune response to heterologous infections and HCMV infection has been associated with reduced survival in elderly people. Patients with chronic lymphocytic leukemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
3
5
0
Order By: Relevance
“…Nevertheless, another large prospective study of ( n = 347) leukemia patients could not demonstrate prognostic effect of HCMV status based on serology. 26 Taken together, our findings support the recent surge of interest in administering ex vivo expanded autologous antigen-specific T cells or the use of tumor lysate pulsed dendritic cells for immunotherapy against GBM. It will be important to combine these cells with immunomodulating drugs or HCMV-specific vaccines to increase T and NK cell persistence and functionality at the severely immunosuppressive tumor frontier.…”
Section: Discussionsupporting
confidence: 80%
“…Nevertheless, another large prospective study of ( n = 347) leukemia patients could not demonstrate prognostic effect of HCMV status based on serology. 26 Taken together, our findings support the recent surge of interest in administering ex vivo expanded autologous antigen-specific T cells or the use of tumor lysate pulsed dendritic cells for immunotherapy against GBM. It will be important to combine these cells with immunomodulating drugs or HCMV-specific vaccines to increase T and NK cell persistence and functionality at the severely immunosuppressive tumor frontier.…”
Section: Discussionsupporting
confidence: 80%
“…To evaluate the latter we focused on the immune response to latent herpesviruses, which drive expanded CD8+ T cell responses in CLL in a mechanism that is thought to reflect a response to increased endogenous viral replication. EBV infection is associated with accelerated time to disease progression in CLL (15) although CMV has no known deleterious effect (16). Of interest, the magnitude of CD8+T cell CMVspecific responses increased with advanced stage disease, in line with a previous study of CD4+ immunity (data not shown) (17).…”
Section: Discussionsupporting
confidence: 71%
“…Cytomegalovirus can cause expansions of the CD8 + and CD4 + T‐cell subsets in CLL (Mackus et al , ; Pourgheysari et al , ), but this has little clinical impact in terms of disease outcome (Parry et al , ). It was possible that the expanded CD4 + T‐cell populations we observed simply reflected a response to chronic CMV infection.…”
Section: Resultsmentioning
confidence: 99%